The Formative and Aesthetic Values of Digital Images and Their Use in Educational Media - Al-Khawaldeh, Nashat Issa; Qudah, Ali (Mohammed Ali) (Dirasat: Human and Social Sciences, 2024)
Study objectives:To activate the formative, aesthetic, and communicative values of digital images through the relationship between graphic elements to create formative data for educational media to achieve communication, interaction, and positive guidance of behavior and perception of information. and activate the role of digital images in creating formative data for educational media to contribute to recognizing the aesthetic and communicative aspects of images as an aspect that captures the visual energy of the recipient. Research methodology: The researcher followed a descriptive and analytical approach to arrive at results consistent with the research objectives. Research findings: The necessity of implementing e-learning, which is the basis for continuous mutual interaction between the sender and receiver through implicit relationships to achieve the desired effect as a result of effective communication interaction in the context of global crises. E-learning. Research summary: Digital images are a tremendous design resource that allows designers to express opinions, ideas, and course content in a variety of attractive ways, in addition to their important communicative role with students. Images are also a visual language and a tool for communication and information transfer, as well as an illustrative aid in the teaching process.